CONGENITAL SCOLIOSIS: AN ARTICLE REVIEW - Komang Agung Irianto; Hizbillah Yazid (Journal Orthopaedi and Traumatology Surabaya)
Background: Congenital Scoliosis (CS) defined as vertebral lateral deviation which forms during the intrauterine embryonic phase, carrying incidence between 0,5-1 per 1000 births. Mortality rate increases in untreated case, especially due to pulmonary problem (40%).